ANALISIS PERILAKU MAHASISWA DALAM PROSES KEPUTUSAN PEMBELIAN PRODUK PANGAN HALAL: Studi Kasus Mahasiswa Universitas Lampung [The Student’s Behavior Analysis in The Buying Process for Halal Food Products: Case Study of The University Lampung] - Andi Antonika; azhari rangga; Fibra Nurainy (Jurnal Teknologi & Industri Hasil Pertanian, 2015)
This research was aimed to analyze student’s behavior and dominant factors in the buying decision for halal food product. The research was conducted by survey method using quisioner to 100 responden. The data were analyzed using descriptive analysis and factor analysis using a Kaiser Meyer Olkin (KMO) method and principal component analysis. The research showed stages in decisions process to purchase of halal food product were need assesment (hunger 30% and life style 30%), information retrieval (directly see 41% and meeting religion 19,9%), alternative evaluation (looking the expiration date 34% and not consume food comes from pork 29%), the purchase decision (always see halal label 85% and not so buy without halal label 51%) and post purchase of food product halal (uncertain eat at canteen college 54% and need to be given a halal certificate any campus canteen 93%). The result of factor analysis showed that there were four factors which affecting the decision. These factors were product’s attributes (product label, making process ingredient and production date); internal factor (income, motivation and lifestyle); religion/culture (halal label and certificate) and the external factor (seller, place and price)Keyword : behavior, halal food, purchasing and student